Regenerasi Monergisitik Sebagai Bentuk Kedaulatan Mutlak Allah dalam Kelahiran Baru Orang Percaya: Kajian Teologis Yohanes 3:1-8 - Pangngaroan , Andarias (Student Evangelical Journal Aiming At Theological Interpretation, 2024)
The doctrine of regeneration has given rise to various different understandings among Christian thinkers and lay congregations. Some believe that being born again is a process that occurs during the Christian life journey. Others associate being born again with the sacrament of water baptism. On the other hand, there is a sharp controversy between the presence (synergistic) or absence (monergistic) of human involvement in the believer's new birth experience. Through a qualitative descriptive method, the author examines the literature sources from related authors. As a result, the researcher found that the new birth is biblically monergistic. This truth is clearly illustrated in the use of the term gennao anothen by Jesus in the Gospel of John 3:3. The analogy of the wind, which was also used by Jesus to describe the independent, mysterious, invisible, vital, non-instrumental nature and the instantaneous action of the Holy Spirit, strengthens the monergistic view. The nature of total depravity in humans is another strong evidence. This fact proves that the new birth of believers is entirely the sovereign work of God without the slightest human contribution.